Anayde Correa de Carvalho: historical legacy for the Brazilian Nursing - Emiliane da Silva Santiago; Paulo Fernando de Souza Campos; Taka Oguisso; Luciana Barizon Luchesi (Universidad de Alicante, 2014)
The biographical narrative is one of the most traditional perspectives of the historical writings. Its methodological renovation means the rescue of the historical trajectories less known, utilizing new documental sets for this activity, such as the oral history. This paper intends to articulate within the scope of the Life Oral History, individual and collective happenings characterized by the personal experience of a nurse who lived the nursing professionalization in Brazil post-1930 - Anayde Correa de Carvalho. The outcomes of this reflection allow considering not only her interpretation about the first associative movements related to the Brazilian nursing which she reported through an extensive documentary but also her production and life experience have contributed to conforming the professional identity of the Brazilian Nursing.